Nonclassicality of vortex airy beams in the Wigner representation - Ooi, Chong Heng Raymond; Chen, R.P. (American Physical Society, 2011)
The Wigner distribution function (WDF) of a vortex Airy beam is calculated analytically. The WDF provides intuitive pictures of the intriguing features of vorticity in phase space. The nonclassical property of the vortex Airy beam and the Airy beam is analyzed through the negative parts of the WDF. The study shows that destructive interference of certain classical waves can mimic nonclassical lights such as those due to quantum effects.